The International Standard for Plasminogen Activator Inhibitor-1 (PAI-1) Activity - Gaffney, Patrick J; Edgell, Tracey A (Thrombosis and Haemostasis, 1996)
Since the finding that plasminogen activator inhibitor-1 (PAI-1) may influence the initiation and progression of acute myocardial infarction, the assay of PAI-1 in plasma using a variety of commercial kits has become commonplace. The need for a standard to define the activity of PAI-1 prompted an international collaborative study (ICS) to calibrate the functional potency of a lyophilised plasma PAI-1 preparation (92/654). Since PAI-1 inhibits the 2 major plasminogen activators, tissue-type plasminogen activator (t-PA) and urinary-type plasminogen activator (u-PA) in an equimolar manner it was important to establish the potency of the PAI-1 inhibitor in terms of both t-PA and u-PA neutralisation. While the ICS indicated a wide spread of data between the laboratories the mean value of 27.5 t-PA neutralisation units and 7.0 u-PA neutralisation units was confirmed by numerous assays at NIBSC using a tedious but technically reliable titration assay procedure. The plasma PAI-1 proposed standard (92/654) was stable at 20° C for 20 months.The Fibrinolysis Subcommittee of the Scientific and Standardization Committee (SSC) of the International Society on Thrombosis and Haemostasis (ISTH), (meeting in Leuven, Belgium in September 1994) has recommended that the plasma PAI-1 (92/654) should be accepted as the International Standard for PAI-1 and should define a unitage in terms of both t-PA and u-PA neutralisation. Subsequently the Expert Committee on Biological Standardization of the World Health Organization (ECBS-WHO) meeting in Geneva, Switzerland in October 1995 approved plasma PAI-1 (92/654) as the International Standard.